Analyzing Event-Related Transients: Confidence Intervals, Permutation Tests, and Consecutive Thresholds - Jean-Richard-dit-Bressel, Philip; Clifford, Colin W. G.; McNally, Gavan P. (Frontiers in Molecular Neuroscience, 2020)
Fibre photometry has enabled neuroscientists to easily measure targeted brain activity patterns in awake, freely behaving animal. A focus of this technique is to identify functionally-relevant changes in activity around particular environmental and/or behavioural events, i.e. event-related activity transients (ERT). A simple and popular approach to identifying ERT is to summarise peri-event signal (e.g. area under the curve [AUC], peak activity, etc) and perform standard analyses on this summary statistic. We highlight the various issues with this approach and overview straightforward alternatives: waveform confidence intervals and permutation tests. We introduce the rationale behind these approaches, describe the results of Monte Carlo simulations evaluating their effectiveness at controlling Type I and Type II error rates, and offer some recommendations for selecting appropriate analysis strategies for fibre photometry experiments.